Halogen species record Antarctic sea ice extent over glacial-interglacial periods - Spolaor, Andrea; VALLELONGA, PAUL TRAVIS; Plane, J. M. C.; KEHRWALD, NATALIE MARIE; GABRIELI, Jacopo; VARIN, Cristiano; TURETTA, Clara; COZZI, Giulio; Kumar, R.; Boutron, C.; BARBANTE, Carlo (Atmospheric Chemistry and Physics, 2013)
Sea ice is an integral part of the earth's climate system because it affects planetary albedo, sea-surface salinity, and the atmosphere-ocean exchange of reactive gases and aerosols. Bromine and iodine chemistry is active at polar sea ice margins with the occurrence of bromine explosions and the biological production of organoiodine from sea ice algae. Satellite measurements demonstrate that concentrations of bromine oxide (BrO) and iodine oxide (IO) decrease over sea ice toward the Antarctic interior. Here we present speciation measurements of bromine and iodine in the TALDICE (TALos Dome Ice CorE) ice core (159 11' E, 72 49' S; 2315 m a.s.l.) spanning the last 215 ky. The Talos Dome ice core is located 250 km inland and is sensitive to marine air masses intruding onto the Antarctic Plateau. Talos Dome bromide (Br−) is positively correlated with temperature and negatively correlated with sodium (Na). Based on the Br−/Na seawater ratio, bromide is depleted in the ice during glacial periods and enriched during interglacial periods. Total iodine, consisting of iodide (I−) and iodate (IO3−), peaks during glacials with lower values during interglacial periods. Although IO3− is considered the most stable iodine species in the atmosphere it was only observed in the TALDICE record during glacial maxima. Sea ice dynamics are arguably the primary driver of halogen fluxes over glacial-interglacial timescales, by altering the distance between the sea ice edge and the Antarctic plateau and by altering the surface area of sea ice available to algal colonization. Based on our results we propose the use of both halogens for examining Antarctic variability of past sea ice extent. © Author (s) 2012.